A study on incidence, predictors and management of hypophosphaemia in a Malaysian ICU - Mat Nor, Mohd Basri; Md Ralib, Azrina; Mohamed, Rozilah @ Abdul Hadi (2011)
Objectives: Hypophosphatemia is frequently encountered in the ICU and is associated with mortality rates up to 30%. Our objectives are to identify the incidence of hypophosphatemia and the associated risk factors. We also want to establish intravenous replacement therapy that is effective for ICU patients. Methods: A prospective non-interventional study assessing adults admitted to ICU in between March and May 2009. Patients aged >18 years old were included; patients without baseline phosphate level and renal failure (±dialysis) were excluded. All patients were evaluated for the occurrence of common risk factors. Association with independent variables that includes age, gender and BMI were verified. Evaluation of IV replacement therapy was done in the treated patients. Statistically significant when p value <0.05. Results: From 50 patients that were reviewed, nine were excluded. There were 66% male and 34% female with mean age 46.88±17.89. The mean ICU stay was 8.00±6.41 days. The incidence of hypophosphatemia was 29% (n=12/41).Gender and creatinine clearance was found to be significantly different between normophosphatemia and hypophosphatemia patients. There was no significant association for each potential risk factor and the number of risk factors (≥3) with the incidence of hypophosphatemia. Multi-linear regression analysis showed that lactate levels, creatinine clearance and pH were significant predictors to the serum phosphate. A significant difference of mean serum phosphate levels were seen after repletion with IV phosphate by total dose of 10, 20 and 40 mmols in the treatment subgroups (mild, moderate and severe). Conclusions: The incidence of hypophosphatemia in our ICU was high and comparable to previous studies. None of the commonly reported risk factors is associated with hypophosphatemia in this studied population. Among all significant correlated variables, only pH was found to be a significant predictor for serum phosphate. Baseline phosphate level may guide the initial replacement dose to prevent delay in normalization of serum level in hypophosphatemia patients.